PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI GURU TERHADAP MUTU LAYANAN DI SMK - Wiretno, Indro; Chiar, M; Syukri, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractTo make a quality school requires a process by providing a best service and quality to customers. provision  of service at  school depend on the ability of a leader who called Principal. The principal has a very important role in influencing his subordinates to be able to work together on achieving the goal that has been settled. Provision   of quality service  at school is very coveted by all citizens of the school and community. Provision of service  at school is one  of form  of the needs of citizens  at school and surrounding communities  in increasing the needs of school facilities and infrastructure. The  factors that can affect the quality of school services in an effort to make a quality school in this research, that is principal leadership and teacher motivation. The  aim of this research to determine the influence of principal’s leadership and teacher’s motivation toward  the quality of State Vocational High School service in Subrayon 1 Sambas Regency.This research suggest 1) to give maximum result in quality school management by giving service to customer, 2) to crate qualified graduates, in teaching and learning process at school, the teacher should give the best service and learning motivation to the  students. 3) principals, teachers and staffs that exist in the school environment provide treatment in serving students, parents and community that priority to customer service satisfaction in the form of prime service. 4) in this research has explained that the quality of service provided by the principal to customers and  teachers motivation to the students in learning will be affect to the quality of the school.      Keywords : Principal’s Leadership, Teacher’s Motivation, quality